Contemporary Ijtihad Deconstruction in The Supreme Court: Wasiat Wajibah as An Alternative for Non-Muslim Heirs in Indonesia - Setyawan, Rahmad; Witro, Doli; Busni, Darti; Kustiawan, Muhamad Taufik; Syahbani, Fatimatuz Zahro Mulia (Jurnal Ilmiah Al-Syir'ah, 2024)
This research aims to critically analyze and deconstruct the rules and theoretical rules of ijtihad and its implementation in resolving contemporary Islamic inheritance law issues that develop in the Supreme Court. The focus of this research is on the wasiat wajibah (compulsory testament) as an alternative for non-Muslim heirs. This field research uses a descriptive-analytical method to explain the conception of ijtihad comprehensively. The primary data for this research came from interviews and observations. Interviews were conducted with several Religious Court Judges and Religious High Court Judges. Meanwhile, observation was conducted in several religious courts and high religious courts. Secondary data came from library data such as Supreme Court decisions on compulsory testaments for non-Muslim heirs. In addition, this library data is also supported by classical books (yellow book), scientific articles, internet websites, etc., related to the research topic. In several of its decisions, this study found that the Supreme Court has carried out modern ijtihad in Islamic inheritance law by providing an alternative law in the form of a compulsory testament for non-Muslim heirs to enjoy the inheritance of Muslim heirs. This alternative law is a product of the ijtihad of judges through the renewal of ijtihad methodology in the context of legal discovery (rechtvinding), which aims to distribute a sense of justice to parties prevented from getting inherited property.  The birth of several Supreme Court decisions, such as decisions number 16 K/AG/2010, 218 K/AG/2016, and 331 K/AG/2018, which provide legal alternatives in the form of compulsory testaments for non-Muslim heirs, is a historical necessity that must be interpreted positively for the sake of future history.